KARAKTERISASI DAN HUBUNGAN KEKERABATAN 13 GENOTIPE SORGUM (Sorghum bicolor (L.) Mouch KOLEKSI BATAN - Ricardo Panjaitan; Elza Zuhry; Deviona ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of the research was to study the agronomic characteristics ofsorghum and studying genetic relationships genotypes of 13 sweet sorghum. Thisresearch has been carried on in the field experiment and Plant BreedingLaboratory, Faculty of Agriculture, University of Riau, Pekanbaru, from April2013 to September 2013.The data were examined by analysis of variance consistof 13 treatments and 3 replications that contained 39 experimmental units. Thesetreatments consist of BATAN’s sweet sorghum strains, there are Patir-1, Patir-2,Patir-3, Patir-4, Patir-5, Patir-6, Patir-7, Patir-8, Patir-9, Patir-10 and 3 sweetSorghum varieties as a comparison, there are Kawali, Mandau and Pahat.GenotypePatir-10 has the highest of seed weight are 3.78 ton/ha compare to othergenotypes. The results of the research showed that clusters are the differencesand similarities between the 13 sorghum genotypes tested on quantitative andqualitative variables. Based on the cluster analysisPatir 2 and Patir 3 are genotype that has nearst genetic with the lowest genetic distance is 1.71. Patir 9 and Mandau have farthest genetic relationship with the highest genetic distance is 84.24. Keywords : characteristic, relationship, sorghum and Cluster Analysis.